A Clinical Feasibility Study of the Forensic Psychiatry and Violence Oxford (FoVOx) Tool - Cornish, R; Lewis, A; Parry, OC; Ciobanasu, O; Mallett, S; Fazel, S (Frontiers Media, 2019)
Background: Risk assessment informs decisions around admission to and discharge from secure psychiatric hospital and contributes to treatment and supervision. There are advantages to using brief, scalable, free online tools with similar accuracy to instruments currently used. We undertook a study of one such risk assessment, the Forensic Psychiatry and Violence Oxford (FoVOx) tool, examining its acceptability, feasibility, and practicality.